Synthesis of Linear Aza and Thio Analogues of Acetogenins and Evaluation of Their Cytotoxicity. Issue 30 (9th September 2013) - Villo, Piret; Toom, Lauri; Eriste, Elo; Vares, Lauri
Abstract: We report the stereoselective synthesis of thio and aza analogues of Annonaceous acetogenins. The synthetic route allows easy variation of the stereochemistry and of the thio‐ and aza‐fragments. Kinetic resolution of terminal bis‐epoxides was used to set two remote stereocentres with high enantio‐ and diastereoselectivities in one step. The cytotoxicity of the analogues was assessed using the HeLa cell line. Abstract : Four aza and two thio analogues of Annonaceous acetogenins were synthesized according to a general synthetic route. Two remote stereocentres in the analogues were set with high enantio‐ and diastereoselectivity in one step by hydrolytic kinetic resolution of a terminal bis‐epoxide.